(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
A novel coronavirus (COVID-19) causes an outbreak of viral pneumonia in Wuhan, Hubei province, China. In this paper, the deterministic compartmental model is given based on the clinical progression of the disease and the intervention measures implemented by the Chinese authorities. Simulations of the model are given to estimate the basic reproduction number for COVID-19 based on the daily reported cases from China CDC. The basic reproduction number of the model is used to assess the transmissibility of COVID-19. The results indicate that COVID-19 will be controlled at the end of March if there are no imported infections people into China. Then the first-level public health emergency response can be adjusted to the second-level or the higher-level response.